Upland pioneers: an introduction - Stolz, Rosalie; Tappe, Oliver (Social anthropology, 2021)
Drawing on various ethnographic case studies from upland Southeast Asia, this special issue explores uplanders’ pioneering agency and challenges the stereotype of the remote and marginal uplander. We consider upland areas as dynamic sites of future-making and change - initiated by pioneering individuals or local elites who seek out and explore different potential sources of (economic and spiritual) potency. By using the figure of the pioneer as heuristic device, we realign our ethnographic gaze on uplanders by giving particular emphasis to: (1) agents of sociopolitical dynamics in Zomia, (2) questions of remoteness and pioneering mobility, (3) old and new sources of potency, from ‘the state’ to the religious domain, (4) aspirations and future-making and (5) pioneers of change and emergent elites.
Gesehen am 11.11.2021